Task-Based Language Teaching: An Experimental Study of the Application of Task-Based Language Teaching in Arabic Speaking Skills - Maghfiroh, Siti; Nurhamim, Nurhamim; Ubaidillah, Ubaidillah (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
Learning to speak Arabic, students are expected to be able to communicate well using Arabic in accordance with social and cultural developments. However, the lack of Arabic speaking skills at Nahdlatul Ulum Islamic boarding school is the basis of this research. Therefore, the purpose of this study is to apply the Task-Based Language Teaching (TBLT) method to improve Arabic speaking skills. This study employs quantitative techniques and a one-group pretest-posttest experimental-pre-experimental design. The research data were obtained from observation, interviews, oral tests, and documentation. A T-test was used to see the difference in scores before and after treatment. The findings of this study indicate an increase in Arabic speaking skills. The average score of students after being given treatment with the TBLT method was 71.74 higher than before being given treatment 44.61. The results of the paired sample t-test indicate a significance value of 0.00, which is less than 0.05. This indicates that a considerable influence is present. Further research with a more comprehensive design to test the effectiveness of the TBLT method in more depth.